THEORY OF EM MONITORING OF SEA BOTTOM GEOTHERMAL AREAS - Ershov S.; Mikhaylovskaya I.; Novik O. (My University, 2006)
Monitoring of geophysical conditions of marine sedimentary basins is necessary for predicting seismic events and for adaptation of geothermal technologies for seismically active (as a rule) sea bottom geothermal areas. These conditions are characterized by seismo-hydro-electromagnetic (EM) geophysical field interaction in the presence of gravity. Based on the main physical principles, geophysical and petrophysical data, we formulate a mathematical model of seismo-hydro-EM interaction in a basin of a marginal sea and calculate the transformation of a seismic excitation in the upper mantle under the central part of the sea of Japan into the low-frequency (0.1 to 10 Hz) EM signals at the top of the sea bottom sedimentary layer, at the sea surface and in the atmosphere up to the lower boundary of the ionosphere. Physics of the EM generation and propagation process is shown including: generation of EM waves in the upper mantle layer M by a seismic wave from under M, spatial modulation of diffusive EM waves by a seismic wave, stopping of the EM wave arrived (before the seismic P wave) from the upper mantle at the top of the sediments because of the high electric conductivity of seawater (3.5 S/m), immediate penetration of the EM wave through the seawater thickness after the delayed seismic P wave shock into the sea bottom, and EM emission from the sea surface into the atmosphere. Let us note that the EM signal in the sea bottom sediments is the first measurable signal of a seismic activation of geological structures beneath the seafloor and this signal is protected by seawater from the influence ionosphere disturbances. Amplitude of the computed magnetic signals (300, 200, 50, and 30 pT at the ocean-atmosphere interface and at the height of 10, 30 and 50 km, respectively), their predominant frequency (0.25 Hz), the delay of the seismic P wave in regard to the magnetic signal for the receivers at the shore (20 s), the amplitude of temperature disturbances in sediments (up to 0.02 K), the parameters of the long (150 km) tsunami wave of a small (up to 20 cm) amplitude far from the shore and other values that characterize the seismo-hydro-EM process are of the orders observed. Recommendations for the EM monitoring of dynamic processes beneath seafloor geothermal areas are given. © 2005 Elsevier B.V. All rights reserved.
Keywords: EARTHQUAKE MONITORING; GEOTHERMAL AREAS; MATHEMATICAL MODELS; SEA BOTTOM